PESQUISA E INOVAÇÕES SOBRE TECNOLOGIAS ASSISTIVAS: Recursos Educacionais da UNA.SUS/UFMA para Daltônicos - BACELAR, Camilla Costa (2024)
This dissertation addresses the problem of including people with color blindness in digital education. The central problem identified is the difficulty that these individuals face when using digital educational resources due to impaired color perception, which can compromise the understanding of the content and the educational inclusion of these users. The general objective of the research is to analyze assistive technologies for people with color blindness applied in digital educational resources of UNA- SUS/UFMA educational content. Specific objectives include evaluating the effectiveness of these assistive technologies in understanding and including users, applying the technologies to educational content, and evaluating users' perceptions after modifying the content. To achieve these objectives, the research used an case study method that involved the application of different assistive technology filters to digital educational resources and the subsequent evaluation of the perception of colorblind users. The “Color Enhancer” tool was one of the main features tested, being applied to simulate the vision of individuals with different types of color blindness and adjust the contrast of images according to WCAG 2.0 guidelines. The research results indicated that, although some assistive technologies improved the perception of textual elements, there were significant disagreements in effectiveness for pictorial elements. Data analysis revealed that, while technologies helped in identifying texts and illustrations, there are still considerable challenges in interpreting images, highlighting the need for further studies and development of more effective tools.